Respiratory Rate Difference Before and After Pursed Lip Breathing Exercise on Asthma Patient in Pulmonary Polyclinic, TNI AU DR. M. Salamun Bandung Hospital - Sulistiyawati , Arie; Pendet, Ni Made Diah Pusparini (Basic and Applied Nursing Research Journal, 2020)
Introduction: Asthma is a reversible disease characterized by airway obstruction which tends to relapse due to certain factors. Asthma required adequate management to minimalize the frequently of the symptoms occurred and not become a burden for its sufferers. Pursed-Lip breathing (PLB) is an effective breathing technique used in managing asthma symptoms. This study aimed to know the difference in the respiratory rate (RR) before and after the PLB exercise on the asthma patients in Pulmonary Clinic, TNI AU dr. M Salamun Bandung Hospital. Method: A quasi-experimental study with a non-equivalent control group approach was used for this experiment. Of 106 asthma patients, 51 patients who met the inclusion criteria were chosen to participate in this study. The participants were asked to do a PLB exercise based on the standard operating procedure of PLB provided by the researcher. Results: The data analysis showed that there was a significant difference in the RR before and after the PLB exercise with an average of 23.90 and 19.94 (p<0.05), respectively. Conclusions: This result indicated that PLB could affect the RR on asthma patients in Pulmonary Polyclinic, TNI AU dr. M Salamun Bandung Hospital.